Decisional conflict amongst women undergoing caesarean section in health facilities in Ibadan (2023)
BACKGROUND: Despite the global trend of increasing caesarean section rates, aversion to this procedure is common among Nigerian women. This gives rise to conflict during counselling and consent taking for the procedure. OBJECTIVE: This study was done to assess decisional conflict in women undergoing caesarean section. METHODS: This was a prospective cross-sectional study among four hundred and seven booked women undergoing elective caesarean section at secondary and tertiary health facilities in Ibadan, Nigeria. A multi-stage sampling method was used in the selection of participants and informed consent was obtained. The survey instrument was an interviewer-administered questionnaire during the counselling session before the surgery. The decisional conflict scale (DCS), low literacy version was used to quantify decisional conflict. Data was entered into SPSS version 21. The statistical level of significance was set at less than 5%. RESULTS: Most (73.5%) participants booked late for antenatal care and had a tertiary level of education (67.6%). A majority, 316 (77.6%) were not accompanied to antenatal visits. The husband (58.7%) was the sole decision maker with respect to health issues. Eighty-six participants (21.1%) experienced significant decisional conflict. The mean decisional conflict score in those who experienced decisional conflict was 41.1 ± 14.6. Recruitment site (p=<0.001), educational level (p=<0.001), and family fecundity (p=0.009) were predictive of having decisional conflict. CONCLUSION: One in five women undergoing caesarean section experience significant decisional conflict, so we recommend the application of the decisional conflict scale to improve counselling of patients having difficulties in giving informed consent. WAJM 2023; 40(3): 269–276.